Persepsi ahli gizi di Indonesia terhadap penerapan nutritional care process (NCP) di rumah sakit - Yosephin Anandati Pranoto; Susetyowati Susetyowati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2022)
Dietitians’ perception of the implementation of the nutrition care process (NCP) in IndonesiaBackground: The nutrition care process (NCP) developed by The Academy of Nutrition and Dietetics was adopted and implemented in Indonesia. Some hospitals in Indonesia do not have a proper facility to support dietitians to implement NCP optimally.Objective: To evaluate dietitians’ perception of the NCP implementation in hospital settings in Indonesia.Methods: This study was a cross-sectional design with dietitians who have been working in a hospital as the study subject. Data were collected by questionnaire. Each subject answered questions on general data, nutrition screening practice, and 20 questions about the NCP implementation. The perception score is ranged from one(1) for ‘strongly disagree’ to five(5) for ‘strongly agree.’ The score was summarized and categorized into two groups ‘good’ and ‘less’ positive perception. Univariate and bivariate analysis was used to evaluate the data statistically. Results: More than half of the participants have a good/positive perception of NCP implementation (62.5%). There was a significant association between the level of education and nutrition screening training to other health workers' perceptions statistically. Conclusion: NCP has been implemented very well in a hospital setting in Indonesia. There are improvements needed in some key aspects to improve the quality of the nutrition care process in the hospital, especially for each dietitian to have a better and more standardized perception nationally on implementing NCP.